Investigating the Strategies for Supply Chain Agility and Competitiveness - Perera, Samudi; Soosay, Claudine; Sandhu, Sukhbir (Asian Journal of Business and Accounting, 2019)
Manuscript type: Research paper Research aims: This study explores the strategies that enable firms to establish supply chain agility and competitiveness in Australian manufacturing firms. Design/Methodology/Approach: Using a case study approach, interviews are conducted with eight Australian manufacturing firms. Underpinned by the dynamic capability perspective, data are then thematically analysed to derive the findings. Research findings: Agility strategies are based on collaborative efforts, requiring information sharing among firms in the supply chain and diversifying core competencies in a strategic manner to remain competitive. Theoretical contribution/Originality: This study shows how dynamic capabilities foster competitive advantage. It identifies both the strategic and operational agility which enable firms to respond to market changes and to remain competitive. Practitioner/Policy implication: The manufacturing industry in Australia is undergoing a transition where Australian manufacturers need to transform and be more agile by leveraging their competencies and supply chains collectively. Research limitation/implications: The results are based on a crosssectional study of firms identified from the Australian manufacturing industry. Keywords: Agility, Australian Manufacturing, Operations, Strategy, Supply Chains JEL Classification: I3, M14